2017
DOI: 10.1038/bjc.2017.413
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus platinum-based chemotherapy for first-line treatment of hepatocholangiocarcinoma: an AGEO French multicentre retrospective study

Abstract: Gemcitabine plus platinum-based chemotherapy is effective as first-line for advanced cHCC-ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 30 publications
5
48
0
1
Order By: Relevance
“…In a French multicenter retrospective study, 30 patients with advanced HCC-CC received GEMOX (n = 18, 60%), GEMOX plus bevacizumab (n = 9, 30%) or GEM+CDDP (n = 3, 10%). In patients treated with gemcitabine combined with cisplatin or oxaliplatin, the median PFS and OS were 9.0 months and 16.2 months, respectively, in line with the results obtained in CC patients [74]. There were no differences in outcomes between the three treatment regimens.…”
Section: Chemotherapysupporting
confidence: 83%
“…In a French multicenter retrospective study, 30 patients with advanced HCC-CC received GEMOX (n = 18, 60%), GEMOX plus bevacizumab (n = 9, 30%) or GEM+CDDP (n = 3, 10%). In patients treated with gemcitabine combined with cisplatin or oxaliplatin, the median PFS and OS were 9.0 months and 16.2 months, respectively, in line with the results obtained in CC patients [74]. There were no differences in outcomes between the three treatment regimens.…”
Section: Chemotherapysupporting
confidence: 83%
“…While surgical techniques have expanded in recent years, allowing for curative approaches even for advanced Klatskin tumors applying procedures such as associating liver partition and portal vein ligation (ALPPS) and portal vein embolization (PVE) with subsequent extended liver resection, intrahepatic cholangiocarcinoma can rarely be resected in a curative manner [16,17]. Moreover, biliary tract cancer shows poor response rates to systemic chemotherapy, with overall survival previously reported for gemcitabine monotherapy of 8.1 months and gemcitabine plus cisplatin of 11.7 months [5]; 13.8 months for intrahepatic cholangiocarcinoma [18] and 16.2 months for hepatocholangiocarcinoma [19]. A recent post-hoc analysis of three large clinical trials on advanced ICC showed survival rates of 16.7 months following 3 to 6 months of chemotherapy, which likely reflects improved patient selection and improvements in chemotherapy regimens [6].…”
Section: Discussionmentioning
confidence: 99%
“…The comparative data on systemic therapy in cHCC-ICC is sparse, but tends to favor the efficacy of chemotherapy over sorafenib (77,92,93). In small retrospective studies (n = 41, 28 and 17), cytotoxic regimens seem to achieve a reasonable response rate and modest mOS benefit (77,92,93).…”
Section: Systemic Treatment Optionsmentioning
confidence: 99%
“…The comparative data on systemic therapy in cHCC-ICC is sparse, but tends to favor the efficacy of chemotherapy over sorafenib (77,92,93). In small retrospective studies (n = 41, 28 and 17), cytotoxic regimens seem to achieve a reasonable response rate and modest mOS benefit (77,92,93). In the largest of these cohorts, there were no recorded objective responses for sorafenib monotherapy (n = 5 evaluable), the median progression free survival (mPFS) was 4.8 m (n = 7) and mOS was 9.6 m (n = 7), whereas for gemcitabine-cisplatin doublet chemotherapy, the partial response rate was 24% (9/37 evaluable), mPFS was 8.0 m (n = 41), and mOS was 11.5 m (n = 41) (77).…”
Section: Systemic Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation